Evaluating Different Vaccine Routes Against Coccidiosis - Saad, Marina Bolzani; Bona, Tania Dello Monaco Martins; Serafini, Clovis Augusto Versalli; Romani, Francine; Alvarez, Joelma Moura; Lourenco, Mariana Camargo; Santin, Elizabeth (International Journal of Poultry Science, 2009)
The effect of coccidiosis vaccine route on animal development and the efficiency of different routes to protect birds against different Eimeria challenges were evaluated. 135 Isa Brown® birds were used in two experimental phases. In the first phase, the birds were distributed in three treatments: non-vaccinated, vaccinated against coccidiosis by water and vaccinated by spray. In the second phase, these birds were challenged separately with different eimeria species oocysts (E. maximum, E. acervulina, E. tenella and E. necatrix). Weight gain, relative weight of Fabricius bursa, degrees of lesions in the intestines and counting of oocysts in the coproparasitological examination were evaluated. As a result, in most cases, birds challenged with different eimeria species and vaccinated against coccidiosis, by water or spray, showed better physical conditions, mainly by: best weight gain and lower intestinal lesions scores, compared to the birds challenged and non-vaccinated. Another interesting result refers to the different vaccine routes, showing no significant difference regarding the effectiveness of the vaccine and the vaccine reaction in animals.